Hypoxia Inducible Factor-1α: The Curator of Gut Homeostasis - Kumar, Tarun; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Cellular and Infection Microbiology, 2020)
The human gut microbiome is a stratified and resilient ecosystem co-inhabited by a diverse and dynamic pool of microorganisms. Microbial selection, establishment, and colonization are modulated through a complex molecular network of host-microbial interactions. These molecular bioprocesses ensure the taxonomic composition of the mature human gut microbiome. The human gut microbiome plays a vital role in host health; otherwise, any microbial dysbiosis could predispose to the onset of physiological and metabolic disorder/s. Focussed research are being carried out to identify key molecular agents defining gut homeostasis. These molecules hold the potential to develop effective therapeutic solutions for microbial dysbiosis-associated human disorders. Of these, Hypoxia-inducible factor-1α (HIF-1α) is a central player in host-microbial crosstalk to maintain gut homeostasis. Human gut microbial metabolites regulate its cellular stability, which in turn regulates various cellular processes required for the stable gut microbiome. In the present review, an effort has been made to summarize the key role of HIF-1α to maintain gut homeostasis.